Robust bin-picking system using tactile sensor. (17th April 2020) - Tajima, Sho; Wakamatsu, Seiji; Abe, Taiki; Tennomi, Masanari; Morita, Koki; Ubata, Hirotoshi; Okamura, Atsushi; Hirai, Yuji; Morino, Kota; Suzuki, Yosuke; Tsuji, Tokuo; Yamazaki, Kimitoshi; et al.
ABSTRACT: This paper presents a robust bin-picking system utilizing tactile sensors and a vision sensor. The object position and orientation are estimated using a fast template-matching method through the vision sensor. When a robot picks up an object, the tactile sensors detect the success or failure of the grasping, and a force sensor detects the contact with the environment. A weight sensor is also used to judge whether the lifting of the object has been successful. The robust and efficient bin-picking system presented herein is implemented through the integration of different sensors. In particular, the tactile sensors realize rope-shaped object picking that has yet to be made possible with conventional picking systems. The effectiveness of the proposed method was confirmed through grasping experiments and in a competitive event at the World Robot Challenge 2018. GRAPHICAL ABSTRACT: